Mini-thoracostomy with vacuum-assisted closure: a minimally invasive alternative to open-window thoracostomy - Alessandro Wasum Mariani; João Bruno Ribeiro Machado Lisboa; Guilherme de Abreu Rodrigues; Ester Moraes Avila; Ricardo Mingarini Terra; Paulo Manuel Pêgo-Fernandes (Jornal Brasileiro de Pneumologia, 2018)
ABSTRACT Thoracostomy is a common treatment option for patients with stage III pleural empyema who do not tolerate pulmonary decortication. However, thoracostomy is considered mutilating because it involves a thoracic stoma, the closure of which can take years or require further surgery. A new, minimally invasive technique that uses the vacuum-assisted closure has been proposed as an alternative to thoracostomy. This study aims to analyze the safety and effectiveness of mini-thoracostomy with vacuum-assisted closure in an initial sample of patients.